What is the best treatment for REM sleep behavior disorder (RBD)?. Issue 1 (January 2017) - Strange, Jehu; Foley, Edward
Abstract : EVIDENCE‐BASED ANSWER : In patients with RBD, melatonin decreases the amount of REM sleep without atonia and improves subjective symptom scores (SOR: C, single small RCT). Clonazepam and melatonin are associated with reduced REM sleep behaviors and injuries (SOR: C, single descriptive survey). A bed alarm may prevent injury in patients with medication‐refractory RBD (SOR: C, small case series).